Effect of boundary factor and material property on single square honeycomb sandwich panel subjected to quasi-static compression loading - Ma, Quanjin; Kuai, Tengfei; M. R. M., Rejab; Manoj Kumar, Nallapaneni; M. S., Idris; Abdullah, M. H. (Faculty Mechanical Engineering, UMP, 2020)
This paper is aimed to investigate the crushing response of single square honeycomb panels under quasi-static compression loading. Two types of materials are used in this study, which refers to 100 % polylactic acid (PLA) and 70 % PLA filled 30 % carbon fibre (PLA/CF). Single honeycomb panels were fabricated through additive manufacturing technique, and assembled using slotting technique. The effect of boundary factor on the single square honeycomb panels have been studied, which refers to none, single-side, double-side boundary conditions. The effect of material properties on the crushing response has also involved. For the tensile test, it was concluded that the PLA/CF specimen offered the higher young modulus with 428.75 MPa than 360.76 MPa of PLA specimen. For the quasi-static compression test, the compressive modulus and strength of the single honeycomb sandwich panel showed 489.69 MPa and 18.32 MPa with boundary type 1, which provided the highest value compared to other two boundary condition types. Moreover, the square honeycomb sandwich panels with PLA/CF material and type 3 boundary condition offered the better crushing performance on energy absorption (EA) with 66.42 kJ and specific energy absorption (SEA) with 2282.47 kJ/kg. In addition, the crushing behaviour and failure mode were also involved and discussed in this study.